Accelerated Tissue Processing With Minimal Formalin Fixation Time for 9-Gauge Vacuum-Assisted Breast Biopsy Specimens: A Proof of Principle. Issue 1 (15th August 2019) - Bulte, Joris P; Halilovic, Altuna; Burgers, Lambert J M; Diepenbroek, Coos J M; de la Roij, Robin A K; Mann, Ritse M; van der Leest, Marloes; van Cleef, Patricia H J; Strobbe, Luc J A; de Wilt, Johannes H W; Bult, Peter
Abstract: Objectives: Vacuum-assisted biopsy (VAB) of the breast seems unsuitable for rapid processing due to large size. We tested microwave-based acceleration. Methods: As a proof-of-principle study, 9-gauge VAB specimens were taken from eight mastectomy specimens. Forty-two biopsy specimens were processed. Quality of H&E was evaluated in 84 slides, and estrogen receptor (ER), progesterone receptor (PR), E-cadherin, and human epidermal growth factor receptor 2 (HER2) stains were evaluated in six slides. Preoperative biopsy specimens were used as a control. Results: Diagnostic quality of H&E slides was good in 87%, reasonable in 12%, and low in 1%. Quality of E-cadherin was good in 75% and reasonable in 25%. Quality of ER was good in 83% and reasonable in 17%. PR and both HER2 immunohistochemistry and fluorescence in situ hybridization were good in all slides. Quality of experimental slides was similar to control slides. Conclusions: Nine-gauge VAB specimens can be processed within 4 hours. Slides are suitable for all routine pathologic stains. This enables a same-day diagnosis.